Immunoglobulin E (IgE)-Mediated Food Allergy in Children: Epidemiology, Pathogenesis, Diagnosis, Prevention, and Management - Simona Barni; Giulia Liccioli; Lucrezia Sarti; Mattia Giovannini; Elio Novembre; Francesca Mori (Medicina, 2020)
A food allergy is an immunoglobulin E (IgE)-mediated hypersensitive reaction to food, which consists in the appearance of allergic symptoms; it can vary from common urticaria to even fatal anaphylaxis. The prevalence of food allergies has been increasing in the past twenty years and it represents a major public health problem in industrialized countries. The mechanism that leads to food allergies is the lack of immunologic and clinical tolerance to food allergens. The diagnosis of IgE-mediated food allergies is based on the combined use of a detailed medical history, in-vivo, and in-vitro research of specific IgE, the elimination diet, and the double-blind placebo-controlled food challenge. The only currently available treatment for allergies is the strict elimination diet. This type of attitude, which we could define as “passive”, does not overcome the risk of accidental reactions due to involuntary intake of the culprit food. For food allergy management, an “active” approach is urgently needed, such as specific allergen immunotherapy, which is currently under development and only used for research purposes. This article aims to give an updated review of IgE-mediated food allergies in pediatric populations in terms of epidemiology, pathogenesis, prevention, diagnosis, and management.